BEDAH MAYAT DALAM PERSPEKTIF MAQASHID AL-SYARIAH - armaya azmi (Universitas Islam Negeri Sumatera Utara, 2021)
Corpse Surgery is a contemporary study in Islamic jurisprudence. There is no clear evidence from the Qur'an and Sunnah regarding the law of post mortem or autopsy. However, Islamic law must be responsive to the development of increasingly advanced and dynamic science. This study aims to explore Islamic law related to post mortem. In addition to using a normative approach from a fiqh point of view with various arguments presented by the scholars, the author also uses the Maqashid Al-Sharia approach with consideration of benefit as a knife of analysis in research. In the framework of Al-Syatibi, there are five objectives to lowering the Shari'a: 1. Hifz Al-Din 2. Hifz al-Nafs 3 Hifz Al-Nasl 4. Hifz al-Mal , 5. Hifz al-'Aql